DISCOURSE MARKERS IN NEWS ARTICLE OF JAKARTA POST - Agnes Larasati; Ana Shofiana Jamilah; Winarti Winarti (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2023)
This study aimed to analyze Discourse Markers (DMs) found in news article of The Jakarta Post. The writer used a descriptive qualitative method, in which the data were sentences that contain discourse markers in the articles. The data were analyzed by applying the theory of discourse markers from Halliday and Hasan (1976). The result showed there were 81 discourse markers included 54 additive markers, 7 adversative markers, 7 causal markers, and 3 temporal/continuative markers. From the data found it can also be concluded that additive markers are the most frequently used in the article.